Effects of a probiotic-fermented herbal blend on the growth performance, intestinal flora and immune function of chicks infected with Salmonella pullorum - Wang, Yiming; Li, Jiayi; Xie, Yuanhong; Zhang, Hongxing; Jin, Junhua; Xiong, Lixia; Liu, Hui (Poultry science, 2021)
Salmonella pullorum is a highly pathogenic bacteria in poultry industry. However, antibiotics were restricted in many countries because of the increasing risk of antibiotic resistance, Therefore, an environmental friendly and effective alternative strives to be developed. This study investigated the benefit of a probiotic-fermented herbal blend on the growth performance and gut microbiota of newborn broilers infected with S. pullorum. A total of 120 one-day-old dwarf male chicks were randomly allotted to 4 treatment groups, each including 5 replicates of 6 chicks: negative control (NC), positive control (PC), herbal blend (HB), and probiotic-fermented herbal blend (PF). All birds (n = 90), except for those in the NC, were infected with S. pullorum (1.69 × 108 CFU) on day 1. On day 11, body weight (BW), mortality, tissue pathology, cecal colony counts, immune organ indices, cecal mucosa secretory immunoglobulin A (sIgA) concentrations, and cecal cytokine mRNA expression levels were investigated. No mortality was observed after the PF treatment, and less pathological condition was in the ileum, cecum, and liver of HB and PF. BW, average daily gain and average daily feed intake were significant higher in the HB group compared to the PC and were the highest in the PF (P < 0.05). HB treatment significantly increased cecal populations of Lactobacilli, and decreased cecal populations of Escherichia coli and Salmonella, but results were more pronounced in the PF group (P < 0.05). Both HB and PF treatments increased cecal mucosa sIgA compared with the PC (P < 0.05). Tumor necrosis factor alpha and interferon gamma were lowest (P < 0.05) and interleukin 4 was the highest (P < 0.05) in PF, which exhibited similar levels to the NC group. PF treatment significantly improved the development of the thymus and bursa in S. pullorum-infected chicks. In conclusion, PF treatment prevented death, improved growth performance, regulated intestinal flora and enhanced immune ability of in S. pullorum-infected with chicks.